Artifial Intelligence in Interventional Radiology - Saniya Khakwani, Mohammad Waleed Bin Fawad, Touseef Ahmed, Toqeer Hussain, Maryem Arif (Pakistan Journal of Medical & Health Sciences, 2022)
Computerized and Algorithmic tools are used in Artificial intelligence (AI). With the help of these tools, we can quickly get more reliable results by giving input to the computer. Artificial neural networks that are very helpful in terms of different computerized models for learning, including computers and DL, are an advancement in Artificial intelligence. Segmentation, lesion detection, and practices in interventional radiology are the modern applications of Artificial intelligence related to radiology. Artificial intelligence also provides information about a person’s risk of suffering from a disease. This also helps to determine the methods for cancer intervention studies. The paper combines evidence-based research with personal expertise to help not just diagnostic imaging trainees and associates but also experienced coworkers considering radiotherapy and chemotherapy therapies.